Customer preferences in car design using kansei engineering and cubic Bezier curve - W N, Hidayah; S H, Yahaya; H, Sihombing; M. S., Salleh; A, AbuAbdullah (International Journal of Engineering and Technology, 2018)
This study is focused on fulfilling the customerâ€™s needs and also the organizationsâ€™ need to organize their genuine phenomenal awareness to find out the customer outline inclinations before creating a specific item since customer design has turned into the essential worry of the organizations' technique. This study is to recognize and analyze the customersâ€™ preferences through car design by using mathematical con-cept known as BÃ©zier curves. The approach is utilized as a part of the study to distinguish and study the consumer loyalty through the cus-tomerâ€™s preferences in designing a car. The cars are then categorized into two types which City cars and Sedan cars. These categories are controlled by the eight segments of cubic BÃ©zier function. The customerâ€™s preferences towards car design can be denoted through the use of cubic BÃ©zier curves.Â Â